2014
DOI: 10.2196/jmir.3532
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Tweets as a Supplementary Method of Seasonal Influenza Surveillance

Abstract: BackgroundExisting influenza surveillance in the United States is focused on the collection of data from sentinel physicians and hospitals; however, the compilation and distribution of reports are usually delayed by up to 2 weeks. With the popularity of social media growing, the Internet is a source for syndromic surveillance due to the availability of large amounts of data. In this study, tweets, or posts of 140 characters or less, from the website Twitter were collected and analyzed for their potential as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 20 publications
2
100
0
1
Order By: Relevance
“…The growing popularity of Twitter among teenagers and young adults may provide opportunities for understanding indoor tanning behaviors and resulting injuries. The social networking service has been used to track the spread of infectious diseases such as influenza [11], H1N1 [12], pertussis [13], and foodborne illness [14]. Similar to foodborne illnesses, acute health consequences of tanning bed use, such as burns, are not routinely monitored or reported.…”
Section: Introductionmentioning
confidence: 99%
“…The growing popularity of Twitter among teenagers and young adults may provide opportunities for understanding indoor tanning behaviors and resulting injuries. The social networking service has been used to track the spread of infectious diseases such as influenza [11], H1N1 [12], pertussis [13], and foodborne illness [14]. Similar to foodborne illnesses, acute health consequences of tanning bed use, such as burns, are not routinely monitored or reported.…”
Section: Introductionmentioning
confidence: 99%
“…Through analysis of information flow, Big Data analytics looks for hidden threads, trends and patterns (Matteson, 2013). Influential examples of Big Data applications include Google Flu Trends, which provides predictions and estimates of influenza activity for more than 25 countries, through aggregation of Google search queries (Pervaiz, Pervaiz, Rehman & Saif, 2012); and the research of Aslam et al (2014), which reported on influenza-like illness rates through the collection and analysis of 159,802 tweets. While Big Data analytics is having a wide impact on public health and businesses' commercialization and marketing, its application remains limited in the field of education.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have explored a number of ways in which technology improves humanitarian diagnostics, including the use of mobile phone network data for human mobility mapping and contact tracing (Tatem et al 2009;Aslam et al 2014;Wesolowski et al 2014;Gittelman et al 2015;Bharti et al 2015;Bengtsson et al 2015), and big data or social media scraping for contagion modeling (Brownstein et al 2009;Chunara et al 2012). Such techniques allow humanitarian actors to extract information, diagnosing needs and epidemiological trends without direct contact with affected populations.…”
Section: Diagnosticsmentioning
confidence: 99%